Colonic gallstone ileus treated by a transanal ileus tube followed by spontaneous gallstone dislodgement: A case report. Issue 1 (8th July 2022) - Takagi, Tadataka; Kinoshita, Shoichi; Kawaguchi, Chihiro; Kojima, Kuniyuki; Ueno, Hirotsugu; Nishimura, Naoki; Shimozato, Naotaka; Shirai, Yasuyo; Noguchi, Ryuichi; Ohyama, Takao
Abstract: A 71‐year‐old obese woman was referred to our hospital with lower left abdominal pain. Computed tomography showed a 46 mm elliptic calcification lodged in the sigmoid‐descending colon junction (SDJ), which had been detected 5 years prior but was not within the gall bladder at presentation. Therefore, we diagnosed colonic gallstone ileus with obstructive colitis caused by a gallstone. Colonoscopy revealed a smooth gallstone impacted at the sigmoid‐descending colon junction, which was not fixed and could be pushed proximally with the endoscope. Dislodgement of the stone was unsuccessful with both a large polypectomy snare and a retrieval basket. Considering the high risk of surgery, we chose a non‐surgical treatment strategy for obstructive colitis. Accordingly, a transanal ileus tube was placed to drain the proximal portion of the gallstone. The drainage of the colon by the ileus tube was satisfactory; the proximal colon was decompressed, ameliorating the obstructive colitis. Five days after tube placement, a colonoscopy revealed spontaneous passage of the gallstone into the rectum where it was finally removed. Cholecystocolonic fistula formation was confirmed by magnetic resonance imaging. We decided to surgically close the cholecystocolonic fistula to prevent future retrograde biliary infections. The surgery used a surgical stapler and was successful, with an uneventful postoperative course. Since radical surgical treatment of colonic gallstones and cholecystoenteric fistulas has a risk of postoperative morbidity and mortality, this case illustrates the importance of thoroughly considering nonsurgical interventions and surgeries for the safe treatment of colonic gallstone ileus.